Hedonic and eudaimonic well-being for sustainable development in university students: personality traits or acceptance of change? - Di Fabio, Annamaria; Palazzeschi, Letizia; Bonfiglio, Antonia; Gori, Alessio; Svicher, Andrea (Frontiers in Psychology, 2023)
Introduction The psychology of sustainability and sustainable development aims to contribute to the establishment of a culture of sustainability regarding the 2030 Agenda and its 17 sustainable development goals. Methods In this framework, this study examined the associations between acceptance of change and well-being (hedonic and eudaimonic sides), controlling for the effects of personality traits, in 284 Italian university students. Results Acceptance of change explained additional variance over personality traits regarding hedonic and eudaimonic well-being. Discussion Acceptance of change could thus represent a promising well-being resource from the perspective of strength-based prevention, opening future perspectives to face the challenges of sustainable development, particularly concerning Goal 3 of the 2030 Agenda: “Good health and well-being.”